2009
DOI: 10.1021/ja905819z
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Hydrogen Storage Capacity Using Tetrahydrofuran

Abstract: Hydrogen hydrates with tetrahydrofuran (THF) as a promoter molecule are investigated to probe critical unresolved observations regarding cage occupancy and storage capacity. We adopted a new preparation method, mixing solid powdered THF with ice and pressurizing with hydrogen at 70 MPa and 255 +/- 2 K (these formation conditions are insufficient to form pure hydrogen hydrates). All results from Raman microprobe spectroscopy, powder X-ray diffraction, and gas volumetric analysis show a strong dependence of hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
135
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 166 publications
(141 citation statements)
references
References 21 publications
2
135
0
Order By: Relevance
“…There are several literature works on THF/hydrogen hydrates spanning thermodynamic, kinetic, molecular characterization and morphological observations (Nagai et al, 2008;Ogata et al, 2008;Strobel et al, 2009bStrobel et al, , 2009cSugahara et al, 2009;Veluswamy et al, 2014c). Florusse et al (2004) reported a drastic reduction in hydrogen hydrate forming pressures with the addition of THF as promoter at 5 MPa and 279.6 K. The highest storage capacity of 4.03 wt% was reported by Lee et al (2005) formed using 0.15 mol% THF at 12 MPa and 270 K. However, such a storage capacity could not be reproduced and demonstrated by other researchers.…”
Section: Introductionmentioning
confidence: 99%
“…There are several literature works on THF/hydrogen hydrates spanning thermodynamic, kinetic, molecular characterization and morphological observations (Nagai et al, 2008;Ogata et al, 2008;Strobel et al, 2009bStrobel et al, , 2009cSugahara et al, 2009;Veluswamy et al, 2014c). Florusse et al (2004) reported a drastic reduction in hydrogen hydrate forming pressures with the addition of THF as promoter at 5 MPa and 279.6 K. The highest storage capacity of 4.03 wt% was reported by Lee et al (2005) formed using 0.15 mol% THF at 12 MPa and 270 K. However, such a storage capacity could not be reproduced and demonstrated by other researchers.…”
Section: Introductionmentioning
confidence: 99%
“…Large deposits of natural gas hydrates below the ocean floor and in permafrost regions are potential new energy resources Boswell, 2009). We may also benefit from a series of new technologies based on hydrates (Hu and Ruckenstein, 2006;Sun et al, 2007a;Tsouris et al, 2007;Nagai et al, 2008;Sugahara et al, 2009;Ricaurte et al, 2013;Zhang et al, 2014). On the other hand, gas hydrates may lead to the plugging of equipment in the production and transportation of oil and gas ( Koh et al, 2011;Joshi et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…If the H 2 storage capacity is improved up to that expected in pure H 2 hydrate, the utilization of clathrate hydrates becomes realistic as a future engineering technology [18]. In fact, the technique has been developed to increase the H 2 storage to 3.4 wt% in THF + H 2 hydrate [19].…”
Section: Introductionmentioning
confidence: 99%